MENYELAMI BENAK KOMUNIKATOR (STUDI PADA PEMBUATAN PESAN PADA KESENIAN WAYANG WATON OLEH KOMUNIKATOR) - Seto Herwandito (Cakrawala Jurnal Penelitian Sosial, 2015)
Recently, there are a lot of study about communication done by scholars. Nearly all the aspects such as: Communicator, message, media, channel, communican are examined. Indeed it is very important and cannot be separated. However, we rarely pay attention to the communicators, so the study of communicators in science communication is very rarely done. This research tries to find out about how a Communicator make message, what is in the mind of the Communicator and how this might appear. This type of research is qualitative and using the paradigm of constructionism, and using methods of ethnography of communication, where researchers work directly, live together, feel what is perceived by the Communicator. Because this research is the research/study about Communicator, then the primary data will be one person that is leader of Padepokan Tjipto Boedaja as communicators.The result of this research is there are several stage in order to make message. First is exploration, in this stage a Communicator have realized what she made and how she will make it, Incubation at this stage ideas that had emerged last stored and absolute thinking, and wait for the right time for something. Second is Eliminated in this stage idea/message was born, Third, Execution, when the moment of inspiration or idea/message has appeared so someone will soon to make something. Here's what is known as the stage of Implementation (Fourth). By releasing any results during incubation. Either all the idea is good or less good, muntahkan everything without rest in a form of something planned and Fifth, Evaluation where the communicators will evaluate the ideas/messages he ever made.Keywords: Communicators, Creative Process, Message, Communication